Avaliação do perfil sérico de citocinas e da tempertaura de ovinos submetidos áendotoxemia experimental: Rafael Ferreira de Araújo. - - Araújo, Rafael Ferreira de [UNESP] (2013)
The present study aimed to evaluate the serum cytokine profile and the temperature of the body surface of sheep undergoing experimental endotoxemia. Ten suffolk sheep with approximately four years of age were used. The animals were randomly separated into two groups comprising five animals each: one group was treated with LPS (Escherichia coli 055: B5: Sigma, St. Louis, MO) at a dose of 400 ng/kg, the control group was inoculated with 2 mL of 0.9% physiological solution of sodium chloride (NaCl). We conducted a physical examination of animals at the time of his admission, and blood collection for the profile of cytokines (TNF-α, IL-1β, IL-2 and IL-13), and at 2, 4, 6, 12, 24, 36, 48 and 60 hours after administration of LPS or saline. Cytokines were measured by ELISA. Rectal temperature was measured by a clinical thermometer. The body surface temperature was measured by infrared hand-held and non-contact thermometer and thermography and infrared imaging were done in regions of the forehead, back, underarm, face external and inner thigh, and perineum. Serum levels of cytokines did not change significantly. Rectal temperature peaked at 40.6°C in 4 hours after the LPS inoculation. The body surface temperature, measured by infrared thermography was initially increased at 6 hours after the LPS inoculation, however, the maximum skin temperature was recorded at 12 hours. This situation occurred with the temperature regions of the forehead, back, underarm, face external and internal thigh sheep. This study show for the first time the cytokine profile of sheep submitted to endotoxemia. The results obtained in this study show for the thermography infrared imaging can be used for the analysis of skin temperature of the sheep, so this technique should be incorporated into routine clinical veterinarians as auxiliary tool for early diagnosis of endotoxemia